JANUARY 24 ECONOMIC STABILITY DECISIONS WITH SEPTEMBER 12 MILITARY COUP NEOLIBERALISM ALLIANCE AND THE ROLE OF POLITICAL ISLAM IN THE PROCESS (Third Sector Social Economic Review, 2019)
1980 was a year Turkey witnessed antidemocratic experiences in economic and political sense in the history of the Republic. The January 24 Economic Stability Decisions and the September 12 military coup took place in this year. The January 24 Economic Stability Decisions taken in order to overcome the impasse of import substitution industrialization dictated structural changes to Turkey's economy in time. This process turned into a compulsory obligation with the September 12 military coup. September 12 military intervention, an important step for the establishment of neoliberalism in Turkey, allowed the religious and conservative to assume the representation of neoliberalism and these actors were articulated to the system in economic, political and public spheres. This study focuses on developments in the 70s and 80s when Turgut Özal was the prominent figure and the structural transformation was carried out by the Motherland Party (ANAP) under his leadership. In addition, the study tries to investigate how economic neoliberalism evolved from the economic sphere to the social sphere, the dimensions of the relationship between the January 24 Decisions and the September 12 military coup and the role of Islamists as actors in this process.
Keywords: Neoliberalism; Import Substitution Industrialization; Islamism; January 24 Decisions; The Coup of September 12